2020
DOI: 10.21203/rs.2.19597/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug resistance occurred in a newly characterized preclinical model of lung cancer brain metastasis.

Abstract: Background Cancer metastasis and drug resistance have traditionally been studied separately, though these two lethal pathological phenomena almost always occur concurrently. Brain metastasis occurs in a large proportion of lung cancer patients (~30%). Once diagnosed, patients have a poor prognosis surviving typically less than 1 year due to lack of treatment efficacy. Methods Human metastatic lung cancer cells (PC-9-Br) were injected into the left cardiac ventricle of female athymic nude mice. Brain lesions … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Cisplatin is a common chemotherapy drug used in the treatment of various types of cancer; however, cisplatin also exhibits serious adverse effects, particularly nephrotoxicity and oxidative injury (23,31). Previous studies have reported that the therapeutic efficacy of emodin combined with chemical drugs is higher than that of chemical drugs alone, and that combination treatment also results in fewer adverse effects (7,15,32).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin is a common chemotherapy drug used in the treatment of various types of cancer; however, cisplatin also exhibits serious adverse effects, particularly nephrotoxicity and oxidative injury (23,31). Previous studies have reported that the therapeutic efficacy of emodin combined with chemical drugs is higher than that of chemical drugs alone, and that combination treatment also results in fewer adverse effects (7,15,32).…”
Section: Discussionmentioning
confidence: 99%